I know the world's worst secret : a child's book about living with an alcoholic parent - Sanford, Doris (Multnomah Press, 1987)
Elizabeth, the daughter of an alcoholic mother, tries to carry the burden of taking care of the family. Includes guidelines for adults to help children of alcoholics.